2020
DOI: 10.1101/2020.07.21.20158196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and external validation of machine learning algorithms for postnatal gestational age estimation using clinical data and metabolomic markers

Abstract: Accurate estimates of gestational age at birth are important for preterm birth surveillance but can be challenging to reliably acquire in low and middle income countries. Our objective was to develop machine learning models to accurately estimate gestational age shortly after birth using clinical and metabolic data. We derived and internally validated three models using ELASTIC NET multivariable linear regression in heel prick blood samples and clinical data from a retrospective cohort of newborns from Ontario… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These samples contain information on the metabolic "fingerprint" of infants which can be used to identify whether they are at risk for specific inborn errors of metabolism and other genetic conditions. We previously demonstrated that data from DBS-derived metabolites can also be utilised to accurately estimate gestational age [2][3][4][5][6]. Gestational age dating is challenging in LMICs due to the lack of access to prenatal ultrasound and the unreliability of dating based on the last menstrual period [7,8].…”
Section: Unlocking the Global Health Potential Of Dried Blood Spot Cardsmentioning
confidence: 99%
See 1 more Smart Citation
“…These samples contain information on the metabolic "fingerprint" of infants which can be used to identify whether they are at risk for specific inborn errors of metabolism and other genetic conditions. We previously demonstrated that data from DBS-derived metabolites can also be utilised to accurately estimate gestational age [2][3][4][5][6]. Gestational age dating is challenging in LMICs due to the lack of access to prenatal ultrasound and the unreliability of dating based on the last menstrual period [7,8].…”
Section: Unlocking the Global Health Potential Of Dried Blood Spot Cardsmentioning
confidence: 99%
“…Sample receipt and analysis were integrated into the existing NSO workflow. Further details on analytes measured can be found here [4,5,10]. Priority analysis times were put in place for all biochemical testing and hemoglobinopathy screening, with the goal of completing analysis of priority conditions within 14 days of birth.…”
Section: Dbs Collection Shipping and Analysis In Low-resource Settingsmentioning
confidence: 99%
“…Another challenge is the adaptation of algorithms developed using blood spot data to estimate population rates of SGA. Existing algorithms can be enhanced using machine learning approaches to improve model performance, and could be further reiterated for SGA-specific estimations [ 11 ].…”
Section: Challenges To This Approachmentioning
confidence: 99%
“…In the Bangladeshi cohort, the model correctly estimated ultrasound-validated gestational age to within one week in the majority of infants, and within two weeks in 90-95% of infants using heel prick and cord blood metabolomic markers 6 . We have since developed and internally validated a second generation of models using a machine learning algorithm and have conducted external validation of model performance in newborn data from two cohorts from Zambia and Bangladesh 7 . The successful use of cord blood in estimating gestational age is of particular interest as we encountered barriers to heel prick sample collection in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…While our previous work, and that of others 5,7 , suggests potential value in using dried blood-spot-derived analytes for gestational age assessment, some key questions need to be answered before attempting to utilize this approach widely as a surveillance tool for preterm birth:…”
Section: Introductionmentioning
confidence: 99%